2012
DOI: 10.3109/17453674.2012.727077
|View full text |Cite
|
Sign up to set email alerts
|

Is the transverse acetabular ligament a reliable cup orientation guide?

Abstract: Background and purpose It is controversial whether the transverse acetabular ligament (TAL) is a reliable guide for determining the cup orientation during total hip arthroplasty (THA). We investigated the variations in TAL anatomy and the TAL-guided cup orientation.Methods 80 hips with osteoarthritis secondary to hip dysplasia (OA) and 80 hips with osteonecrosis of the femoral head (ON) were examined. We compared the anatomical anteversion of TAL and the TAL-guided cup orientation in relation to both disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…[23][24][25][26] Our mechanical device was designed so that it can focus on guiding the inclination angle only, if desired, which simplifies both the planning and the execution. For these cases, only a standard AP radiograph is required.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Our mechanical device was designed so that it can focus on guiding the inclination angle only, if desired, which simplifies both the planning and the execution. For these cases, only a standard AP radiograph is required.…”
Section: Introductionmentioning
confidence: 99%
“…The transverse acetabular ligament (TAL) was only used as a landmark during cup positioning in the two cases whose acetabula were less distorted. It has been reported that although TAL may be a good guide in hips with normal anatomy, TAL is not a reliable guide in hips with osteoarthritis secondary to dysplasia for determining optimal cup orientation during THA 20. Anterior and posterior stability were evaluated routinely with the trial components.…”
Section: Methodsmentioning
confidence: 99%
“…Images were rotated to align with the anterior pelvic plane [18]. The line of the superior TAL was established between the posteroinferior and anteroinferior edges of the acetabular rim, as previously reported [11]. The first angle of the TAL for three-dimensional (3D-CT) was measured between the line of the superior edge of the lowest visible vertebra and that of the TAL.…”
Section: Measurementsmentioning
confidence: 99%
“…Archbold et al reported that the transverse acetabular ligament (TAL) and acetabular labrum were useful for determining the anteversion of the acetabular component [7]. TAL has been evaluated as an anatomic landmark for acetabular component orientation [7][8][9][10][11][12][13][14][15][16][17]. The usefulness of TAL as a landmark is still controversial.…”
Section: Introductionmentioning
confidence: 99%